A Worse Place Than Hell: How the Civil War Battle of Fredericksburg Changed a Nation by John Matteson (A Pre-Publication Book Review) - Świerkot, Mariola (Review of International American Studies, 2020)
Mariola Świerkot's review of John Matteson's A Worse Place Than Hell: How the Civil War Battle of Fredericksburg Changed a Nation. W.W. Norton & Company 2021. ISBN 978-0-393-24707-7